Penerapan Model Pembelajaran Inquiry untuk Meningkatan Hasil Belajar PKN tentang Kebebasan Berorganisasi - Kanti Pristiwati (Faculty of Education Universitas Negeri Malang, 2016)
Abstract: Application of Inquiry Learning Model for Improving Learning Outcomes of Civic Education About the Freedom to Organize. The purpose of this research are: (1) describe the application of inquiry learning model that can improve learning outcomes; and (2) describe the learning outcome of students in the subjects of Civic Education on Freedom to Organize the inquiry learning model can improve student learning outcomes Class V SDN Rembang 2 of Blitar. This type of research is the Classroom Action Research, and carried out in two cycles. Each cycle consists of four phases: planning, implementation, observation, and reflection. The results showed that the implementation of inquiry learning model can improve the activity of the teacher, student activities, and student learning outcomes. This is evident from the acquisition value of the average student learning outcomes which have been steadily increasing from the first cycle was 73, and in Cycle II to 83. In addition the percentage of completeness of students in the first cycle was 58% and the second cycle reaches 87, 5%.Abstrak: Penerapan Model Pembelajaran Inquiry Untuk Meningkatan Hasil Belajar Pkn Tentang Kebebasan Berorganisasi. Tujuan penelitian ini adalah: (1) mendeskripsikan penerapan model pembelajaran inquiry yang dapat meningkatkan hasil belajar; dan (2) mendeskripsikan peningkatan hasil belajar siswa dalam mata pelajaran Pendidikan Kewarganegaraan tentang Kebebasan Berorganisasi dengan model pembelajaran inquiry dapat meningkatkan hasil belajar siswa Kelas V SDN Rembang 2 Kota Blitar. Jenis penelitian yang digunakan adalah Penelitian Tindakan Kelas (PTK), dan dilaksanakan dalam 2 siklus. Setiap siklus terdiri dari 4 tahapan yaitu perencanaan, pelaksanaan, observasi, dan refleksi. Hasil penelitian menunjukkan bahwa penerapan model pembelajaran inquiry dapat meningkatkan aktivitas guru, aktivitas siswa, dan hasil belajar siswa. Hal ini terlihat dari perolehan nilai rata-rata hasil belajar siswa yang mengalami peningkatan secara bertahap mulai dari Siklus I sebesar 73, dan pada Siklus II menjadi 83. Selain itu persentase ketuntasan belajar siswa pada Siklus I sebesar 58% dan pada siklus II mencapai 87,5%.